Preparation of engineering staff for the activities under WTO - I. . Biktagirov; A. . Vologdin (Высшее образование в России)
The article is about the productive collaboration of two universities of different types.These universities are KNRTU specializing in preparation of Chemical Engineers, and VAVT specializing in preparation of economists and lawyers in the sphere of international relations. Due to the cooperation of the University and the Academy, professional retraining program named ‘Management of organization’s foreign trade under WTO conditions’ was prepared.